Solution of Non-linear Time-fractional Generalized Hirota-Satsuma Coupled Korteweg-de Vries Equation By Using New Analytical Approach - R. K Bairwa; Sanjeev Tyagi (International Journal of Mathematics And its Applications, 2023)
This paper is concerned with the approximate analytical solution of non-linear time-fractional generalized Hirota-Satsuma Coupled Korteweg-de Vries equation (GHS-cKdV) using an efficient analytical approach, namely the Sumudu transform iterative approach. The proposed approach is an elegant amalgam of the Sumudu transform method and the Iterative method. The time-fractional derivative are described in Caputo sense. The results obtained are graphically shown and demonstrate that the approach is simple to apply and highly efficient to analyze the behavior of non-linear coupled fractional differential equations.